2016
DOI: 10.1371/journal.pone.0147713
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Total Intravenous Anesthesia and Inhalation Anesthesia in Free Flap Surgery of Head and Neck Cancer

Abstract: BackgroundMany studies have evaluated risk factors associated with complications after free flap surgery, but these studies did not evaluate the impact of anesthesia management. The goal of the current study was to evaluate the differences between patients who received inhalation and total intravenous anesthesia (TIVA) in free flap surgery.MethodsOne hundred and fifty-six patients who underwent free flap surgery for head and neck cancer were retrospectively divided into the TIVA (96 patients) and the inhalatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
0
14
2
Order By: Relevance
“…27 Although we excluded patients with a low risk of PPCs and a larger proportion of patients underwent tracheotomy, the observed rate of PPCs in our study was slightly lower than that in the previous study. 2,3,28 This finding may be associated with the improvement in operation time, intravascular volume management, blood loss and transfusion (no patient underwent blood transfusion in this study), etc, which appear to have an important impact on the risk of PPCs during major surgery. 2,29 Thirty-three of the 201 patients in our study had postoperative pneumonia (POP), which is inconsistent with previous reports.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…27 Although we excluded patients with a low risk of PPCs and a larger proportion of patients underwent tracheotomy, the observed rate of PPCs in our study was slightly lower than that in the previous study. 2,3,28 This finding may be associated with the improvement in operation time, intravascular volume management, blood loss and transfusion (no patient underwent blood transfusion in this study), etc, which appear to have an important impact on the risk of PPCs during major surgery. 2,29 Thirty-three of the 201 patients in our study had postoperative pneumonia (POP), which is inconsistent with previous reports.…”
Section: Discussionmentioning
confidence: 64%
“…Perforator-based free flaps have been increasingly used in the repair and reconstruction in head and neck surgery. Previous studies have shown that the incidence of PPCs after free flap surgery is 18.8% to 44.8%, 1,2,3 while that of PPCs in patients undergoing head and neck surgery with tracheotomy is up to 47%. 4 It is a key point for anesthesiologists to prevent and reduce the occurrence of PPCs.…”
Section: Introductionmentioning
confidence: 96%
“…53 Another retrospective study investigated the role of different anesthetic strategy in 156 patients who underwent free flap surgery for head and neck cancer. 54 No differences in hospital mortality or length of stay were observed between groups, probably due also to a little sample. However, patients receiving propofol showed a lower rate of postoperative pulmonary complications, as opposed to those receiving inhalational anesthetics.…”
Section: Current Evidence On the Effects Of Anesthesia On Short And Lmentioning
confidence: 91%
“…However, patients receiving propofol showed a lower rate of postoperative pulmonary complications, as opposed to those receiving inhalational anesthetics. 54 Data from prospective randomized controlled trials are nowadays little. In a small randomized controlled trial, 28 consecutive patients undergoing oncological surgery for urinary bladder cancer were randomized to receive or total intravenous anesthesia or balanced inhalational anesthesia.…”
Section: Current Evidence On the Effects Of Anesthesia On Short And Lmentioning
confidence: 99%
“…[3] Health professionals and the environmental health community have an obligation to inform, advice, and implement changes to address these concerns. [4] There are many comparisons of total intravenous anesthesia (TIVA) and inhalational agents [5][6][7][8][9] , but studies concerning the consumption of anesthetic agents and cost analysis of use in OLV are limited. The present study aims to evaluate the total quantity of intravenous and inhalational anesthetic agents used during OLV and to discuss the aspect of the cost-effectiveness of these two techniques with respect to the current literature.…”
Section: Introductionmentioning
confidence: 99%